Fabrication of highly permeable thin-film composite forward osmosis membrane using poly-l-lysine as an additive in polysulfone substrate - Pham, Tuan Minh; Vo, Thu Anh; Duong, Manh Tuan; Dang, Thom Thi; Do, Van Manh (Vietnam Journal of Science and Technology, 2022)
Forward osmosis (FO) has received considerable interest for water and energy-related applications in recent years. However, FO has not been commercialized yet because of a few reasons. The lack of a high-performance FO membrane is one of the important barriers. To overcome this issue, a novel high-performance thin-film composite (TFC) membrane was successfully fabricated via interfacial polymerization with poly-L-lysine incorporated polysulfone substrate (PSf). Compared to the pristine PSf substrate, the incorporation of lysine (ranging 1 – 15 wt.%) meaningfully alternates the substrates chemical structure, porosity, contact angle, and morphology leading to an enhancement of the lysine -TFC membranes performance. The results showed that the new substrates with higher porosity, more hydrophilic, and smaller in pore size after the introduction of L-lysine. The membrane achieved the highest FO water flux at 15% concentration of lysine and the maximum FO water flux was 35 L/m2.h (LMH) with a comparable specific salt flux (Js/Jw) of 0.002 g/L in the active layer facing the feed side (AL-FS) when 1M NaCl was applied as draw solution. The water flux was increased with increasing concentration of lysine. The addition of poly-L-Lysine in casting solution resulted in a more porous and hydrophilic support layer.